Quality and Variability of Online Available Physical Therapy Protocols From Academic Orthopaedic Surgery Programs for Medial Patellofemoral Ligament Reconstruction. Issue 7 (2nd July 2019) - Lieber, Adam C.; Steinhaus, Michael E.; Liu, Joseph N.; Hurwit, Daniel; Chiaia, Theresa; Strickland, Sabrina M.
Background: Unlike the literature on anterior cruciate ligament reconstruction, studies on medial patellofemoral ligament (MPFL) reconstruction lack evidence-based guidelines regarding postoperative rehabilitation. An effective postoperative protocol may contribute greatly to a successful outcome following MPFL reconstruction, yet the quality and variability of these published protocols remain unknown. Purpose: To assess the quality and variability of MPFL rehabilitation protocols publicly available on the internet and associated with US academic orthopaedic programs. Study Design: Systematic review. Methods: All available isolated MPFL reconstruction rehabilitation protocols from US academic orthopaedic programs participating in the Electronic Residency Application Service were collected and included in this review. These protocols were evaluated for inclusion of various rehabilitation components, the timing of suggested initiation of these activities, and whether the protocol used evaluation-based guidelines. Results: A total of 27 protocols were included. Of these, 25 (93%) recommended immediate postoperative bracing. Time to initiation of full weightbearing ranged from 2 to 8 weeks. The most common strengthening exercises endorsed were quadriceps sets (89%), straight-legged raise (85%), and leg press (81%). The most common proprioception exercises endorsed were balance board (41%), single-legged balance (41%), and TheraBand control (33%). The median time suggested to return to play was 17 weeks. No functional test appeared in the majority of the protocols. Of the 27 protocols, 20 (74%) used evaluation-based guidelines. Conclusion: There is substantial variability in content and timing across rehabilitation protocols following MPFL reconstruction. This lack of clear guidelines can cause confusion among patients, therapists, and surgeons, leading to suboptimal patient outcomes and making it difficult to compare outcomes across the literature.